Language Invective Community Jeneponto (Study Sociolinguistics) - St. Nur Fadillah Abdullah; Usman Usman; Asia M (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract: This study aims to: (1) describe the form of swearing in the Jeneponto community, (2) describe the function of swearing in the Jeneponto community. This type of research is descriptive qualitative research. The focus of this research is the swear language that is often used among the Jeneponto community. The research source is the Sidenre community, Binamu District, Jeneponto Regency. The data collection technique was done by recording technique, listening technique, and note-taking technique. The results of the study found several forms and functions of the use of swear language among the Jeneponto community. The form of swearing language is divided into single basic word forms, derived basic word forms, phrase forms, and clause forms, while the functions of swearing language are divided into expressing anger, expressing anger, as a call for intimacy. Invective language in the Jeneponto community is spoken based on certain needs, such as anger, irritation, and as a call for intimacy. In addition, the use of swear language does not always hurt other people's feelings, you can see it based on the context of its use, be it as a joke, or as an outlet for anger. Keywords: Swearing, Form, Function, Society.